2019
DOI: 10.3168/jds.2018-16016
|View full text |Cite
|
Sign up to set email alerts
|

Colostrum from cows immunized with a veterinary vaccine against bovine rotavirus displays enhanced in vitro anti-human rotavirus activity

Abstract: Human rotaviruses represent a major cause of severe diarrheal disease in infants and young children. The limited impact of oral vaccines on global estimates of rotavirus mortality and the suboptimal use of oral rehydration justify the need for alternative prophylactic and therapeutic strategies, especially for immunocompromised hosts. The protective effects of colostrum-the first milk produced during the initial 24 to 48 h after parturition-are well documented in the literature. In particular, the ingestion of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 61 publications
(75 reference statements)
0
8
0
Order By: Relevance
“…Accordingly, the study of Civra et al (2019) demonstrated that the conventional bovine RV vaccine was sufficient to enhance the antihuman RV protective efficiency of bovine colostrum due to a high titer of cross-reactive anti-human RV IgG. 24 Taken together, these findings indicate a conservative and feasible approach to produce HBC derived formulas that could be exploited in the fight against RV infections in both developed and developing countries. Such preparations could be a way of confronting the RV infections as a complementary strategy, or as a way of prophylaxis by their addition to infant formulas.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Accordingly, the study of Civra et al (2019) demonstrated that the conventional bovine RV vaccine was sufficient to enhance the antihuman RV protective efficiency of bovine colostrum due to a high titer of cross-reactive anti-human RV IgG. 24 Taken together, these findings indicate a conservative and feasible approach to produce HBC derived formulas that could be exploited in the fight against RV infections in both developed and developing countries. Such preparations could be a way of confronting the RV infections as a complementary strategy, or as a way of prophylaxis by their addition to infant formulas.…”
Section: Discussionmentioning
confidence: 99%
“…By vaccinating the cows with a conventional veterinary vaccine against bovine RV rather than a targeted pathogen, they generated HBC on a large scale that could be used as a functional ingredient to prevent and treat RV infections. 24…”
Section: Introductionmentioning
confidence: 99%
“…it has been suggested that bovines have the advantageous ability to generate super-antibodies against other human pathogens (Walker and Burton 2018 ). Colostrum from cows vaccinated with conventional bovine rotavirus vaccine, displayed antibodies with in vitro anti-human rotavirus activity (Civra et al 2019 ). bIgG promotes adaptive antiviral T cell responses and protects against RSV infection in vitro and in vivo.…”
Section: Bovine-derived Productsmentioning
confidence: 99%
“…Composition of BC has been comprehensively reviewed in a companion paper in this supplement [17]. Hyperimmune Bovine Colostrum (HBC) or extracted immunoglobulins for treatment of intestinal infection have been used successfully for treatment of several intestinal infections including rotavirus, Cryptosporidium spp., Shigella spp., and Clostridium difficile [18,19], but these will not be the focus of this article. We searched for both human studies and those using animal models in PubMed, using key words including "colostrum" and "diarrhea", ("IBD" or "Crohn's disease" or "ulcerative colitis"), "necrotizing enterocolitis", "short bowel syndrome", "gut inflammation", "NSAID-induced gut injury", ("cancer" or "malignancy").…”
Section: Introductionmentioning
confidence: 99%